Effect of phenylephrine vs. ephedrine on frontal lobe oxygenation during caesarean section with spinal anesthesia: an open label randomized controlled trial - Foss, Visti T.; Rokamp, Kim Z.; Christensen, Robin D.; Nissen, Peter; Secher, Niels H.; Nielsen, Henning B. (Frontiers in Physiology, 2014)
Background: During caesarean section spinal anaesthesia may provoke maternal hypotension that we prevent by administration of phenylephrine and/or ephedrine. Phenylephrine is however reported to reduce the near infrared spectroscopy-determined frontal lobe oxygenation (ScO2) but whether that is the case for patients exposed to spinal anaesthesia is not known. Objectives: To evaluate the impact of phenylephrine vs. ephedrine on ScO2 during caesarean section with spinal anaesthesia in a single centre, open-label parallel-group study with balanced randomization of 24 women (1:1). Secondary aims were to compare the effect of the two drugs on maternal haemodynamics and foetal heart rate. Intervention: Ephedrine (0.8-3.3 mg/min) vs. phenylephrine infusion (0.02-0.07 mg/min). Results: For the duration of surgery, administration of ephedrine maintained ScO2 (compared to baseline +2.1± 2.8%;mean ± SE, while phenylephrine reduced ScO2 (-8.6 ± 2.8%; p = 0.005) with a 10.7% difference in ScO2 between groups (p=0.0106). Also maternal heart rate was maintained with ephedrine (+3 ± 3 bpm) but decreased with phenylephrine (-11 ± 3 bpm);difference 14 bpm (p=0.0053), but no significant difference in mean arterial pressure (p = 0.1904) or CO (p=0.0683) was observed between groups. The two drugs also elicited an equal increase in foetal heart rate (by 19 ± 3 vs. 18 ± 3 bpm; p=0.744). Conclusion: In the choice between phenylephrine and ephedrine for maintenance of blood pressure during caesarean section with spinal anaesthesia, ephedrine maintains frontal lobe oxygenation and maternal heart rate with a similar increase in foetal heart rate as elicited by phenylephrine. Trial registration: Clinical trials NCT 01509521 and EudraCT 2001 006103 35